Factors Associated with Readmissions in Ischemic Stroke : A Literatur Review - Ni Made Ratih Comala Dewi; Ni Luh Putu Dina Susanti; I Kadek Nuryanto; Ni Kadek Sutini (Babali Publisher, 2025)
Background: Readmission cases among stroke patients are common, with only 15% of patients surviving and avoiding readmissions over a five-year period. Ischemic stroke patients who are readmitted face a higher risk of death and significantly increased healthcare costs. Therefore, identifying factors associated with the readmission of ischemic stroke patients is essential to prevent these occurrences. Methods: Articles were selected following PRISMA Guidelines. A literature review used three journal databases: ScienceDirect, PubMed, and Google Scholar. Keywords were aligned with the Medical Subject Heading (MeSH) terms, including